The Impact of State Funding of Higher Education on Employment and Living Standards in Georgia - Shainidze, Ekaterine; Mamuladze, Nino; Katamadze, Giorgi; Ghoghoberidze, Tamar (European Journal of Sustainable Development, 2024)
State financing of higher education is crucial for promoting innovation and competition, as well as guaranteeing equal opportunities and access to education. This financing facilitates the development of students' potential by providing them with the necessary skills and information to enhance graduation rates and social well-being. Scholarships and grants are implemented to improve student access to education by aligning the financial system with the demands of the job market and educational developments. The aim of the study is to evaluate the impact of financing higher education in Georgia on employment of graduates and well-being of the population. The results of the survey of entrants and students reveal that public awareness of state-funded higher education programs in Georgia is quite low (47.2%). A large part of the graduates (47,8%) provided with various types of state funding during their studies are not employed in their specialty. The impact of the increase in the expenditure on education on the increase in the income of the population is quite low (0.23%). The research concludes that the allocation of public funds for higher education in Georgia does not effectively match the capabilities of graduates with the demands of the labour market. The reason for the mentioned inconsistency is that the requirements of the labor market were not taken into account when determining the directions to be financed. In addition, it is important to note that the demands of the labor market change every year in accordance with the current challenges, therefore the employer also demands relevant skills immediately, which cannot be met by higher education institutions in a short period of time. Despite the above, the involvement of employers in the process of developing educational programs is low and it is mostly formal in nature. When determining the priority educational programs, there is no periodic revision of the directions so that it is adapted to the demands of the labor market. It is necessary to establish partnership relations between employers, higher educational institutions and the state in order to take into account the requirements of the labor market both in the development of educational programs and in the determination of priority educational directions. Enhancing transparency and emphasising practical training in key areas are essential for enhancing the program's efficacy and enhancing the career chances of graduates. These modifications will provide a more favourable return on investment for state education expenditure. Keywords: higher education, state financing, employment, living standards